Performance of Non-Conventional soil Ameliorants in Banana (Musa spp) var. Nendran - Amalendu M.V (Department of Soil Science and Agricultural Chemistry, College of Agriculture, 2019)
An investigation entitled “Performance of non-conventional soil ameliorants in banana (Musa spp) var. Nendran” was carried out at College of Agriculture Padannakad and Regional Agricultural Research Station (RARS) farm Nileshwar from 2017 to 2019. The objective was to study the performance of banana (Musa spp) var. Nendran in initial period with respect to the different non-conventional ameliorants and a subsequent field trial to confirm the importance of these ameliorants throughout the growing period in improving plant health and yield Pot culture study was carried out to evaluate the efficiency of different soil ameliorants in improving soil health as well as crop health with respect to availability of nutrients upto 4 months. The experiment was conducted in Completely Randomized Design (CRD) consisting of 5 treatments and 4 replications with the following treatments; T1 (basal application of Calcium silicate), T2 (Basal application of lime+ silica), T3 (Basal application of dolomite + silica), T4 (Basal application of Gypsum+ silica), control T5 (Basal application of lime as per KAU POP 2016). The biometric observations like the plant height, number of leaves, root length, root diameter and root CEC were periodically recorded. Considering the plant height, pseudostem girth and number of leaves T4 showed superior results. The root characters like root length, root thickness and root CEC were found superior in T4. The field experiment was carried out at Regional Agricultural Research Station (RARS) farm Nileshwar to study the effect of ameliorants on yield and quality of tissue culture banana var. Nendran. It was conducted in randomized block design comprising of 11 treatments and 3 replications. The treatments used in pot culture experiment were used in split doses to manage the soil acidity throughout the growing period of crop. Treatments were T1( Basal application of Calcium silicate), T2 (Basal application of lime + silica), T3 (Basal application of dolomite +silica), T4 (Basal application of Gypsum + silica), T5 (Lime+ silica in 2 splits at 1st and 2nd month after planting), T6 (Dolomite + silica in 2 splits at 1st and 2nd month 140 after planting), T7 (Gypsum + silica in 2 splits at 1st and 2nd month after planting, T8 (Lime+ silica in 3 split doses at 1st month, 2nd month and 4th month after planting),T9 (Dolomite + silica in 3 split doses at 1st month, 2nd month and 4th month after planting), T10 (Gypsum + silica in 3 split doses at 1st month, 2nd month and 4th month after planting), T11 (Application of lime as per KAU POP 2016) as the control. Biometric observations were recorded periodically. Soil and leaf analysis were also carried out at specific intervals of the experiment. The results of the field experiment revealed that among the vegetative characters, plant height, pseudostem girth at 90 cm height, number of leaves, number of functional leaves and number of suckers were superior for T10. Considering the yield attributes like number of hands per bunch (6.33) and number of fingers per hand (8.66) T10 recorded superior results. Treatment T10 recorded the highest bunch weight of 11.24 kg. Among the finger characteristics, average finger breadth (16.00 cm) and average weight of the fingers (225.00 g) is superior in T9 and the finger length (21.30 cm) is superior in T10. Among the treatments T10 recorded minimum days for bunch emergence (186 days), days to harvest (277 days) and days to ripening (4.33 days). Fruit characters like total soluble solids (29.90 0 brix), titrable acidity (0.27 %), reducing sugar (19.00 %), non reducing sugar (4.89 %), shelf life (4.40 days) were found superior in T10. Studies on the soil nutrient status was conducted at 3 months after planting, 6 month after planting and at harvest of the crop. It was revealed that T10 recorded superior results for soil pH and electrical conductivity. Considering the organic carbon content and cation exchange capacity T10 recorded superior results. Available nitrogen, potassium, phosphorus, calcium and sulphur, copper, zinc and silicon was found superior in T10 whereas highest available magnesium content was recorded in T9. In case of available Iron, manganese and exchangeable aluminium T10 gave superior results. Leaf analysis was carried out at bunching and at harvest of the crop and the following results were obtained. Nitrogen, potassium, phosphorus content in the leaf was found superior for T10. The calcium and sulphur content in the leaf was 141 superior for T10 while treatment T9 recorded the highest magnesium uptake. Uptake of micronutrients like zinc, copper and silicon were found superior in T10. Lowest concentration of iron and manganese were recorded in T10. The results from the investigation revealed that the application of non-conventional soil ameliorants increased the nutrient availability in soil thereby increasing the yield and quality of banana. Among them application of gypsum + silica in 3 splits dosses performed well and produced superior results in northern lateritic soils.